2013
DOI: 10.1002/chem.201204157
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Aspects of Gas‐Phase Hydrogen‐Atom Transfer from Methane to [CO].+ and [SiO].+: Why Do They Differ?

Abstract: The reactivity of the two diatomic congeneric systems [CO](·+) and [SiO](·+) towards methane has been investigated by means of mass spectrometry and quantum-chemical calculations. While [CO](·+) gives rise to three different reaction channels, [SiO](·+) reacts only by hydrogen-atom transfer (HAT) from methane under thermal conditions. A theoretical analysis of the respective HAT processes reveals two distinctly different mechanistic pathways for [CO](·+) and [SiO](·+), and a comparison to the higher metal oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 112 publications
1
30
1
1
Order By: Relevance
“…Adapted from Ref. [56]. requires only 63 kJ mol −1 , and is much less energy-demanding than the alternative route.…”
Section: Hat In the Gas Phase: The Mechanistic Scenariosmentioning
confidence: 99%
“…Adapted from Ref. [56]. requires only 63 kJ mol −1 , and is much less energy-demanding than the alternative route.…”
Section: Hat In the Gas Phase: The Mechanistic Scenariosmentioning
confidence: 99%
“…22−27 Rate constant and product branching measurements have been made using selected ion flow tube (SIFT) 25 or ion cyclotron resonance (ICR) techniques. 16,27 It has been shown that the reaction proceeds at the collision rate, and in addition to the HAT pathway, charge-transfer (CH 4 + + CO) and H-atom expulsion (CH 3 CO + + H) products are found. The mechanistic details of the HAT pathway in this reaction have only very recently been tied to experimental results, utilizing ICR methods coupled with quantum chemical calculations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…7 While this indirect mechanism is not a true HAT mechanism as defined above, it represents the preferred pathway in almost all of the diatomic systems studied. 12−15 An exception is the reaction of CO + with methane, 16 an interesting case study for two reasons. First, while heavier members of carbon's group prefer the indirect pathway where the metal or metalloid facilitates HAT, CO + opts for the direct HAT mechanism.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bettinger et al [31] extended this research to electrophilic singlet borylnitrene compounds and found that certain borylnitrenes are good reagents for the transformation of methane. Hydrogen atom abstraction from CH 4 is considered to be a key step in the oxidative dehydrogenation and dimerization of methane [32][33][34], and abstraction by metal-free radical cation oxides, such as [P 4 O 10 ] + and [SO 2 ] + at room temperature have been reported by Schwarz et al [35,36] and de Petris et al [37]. The gas-phase experiments on methane activation are helpful in revealing the mechanistic details of the elementary steps in the condensed phase [11].…”
mentioning
confidence: 99%